Gamma-ray attenuation properties of some heavy metal ferroalloys for potential applications - Buyukyildiz, Mehmet; Thakur, Sonika; Levet, Aytac; Kaur, Parminder (Pergamon-Elsevier Science Ltd, 2024)
In the present study, ferro manganese (HC), ferro chromium (MC), ferro silicon zirconium (FeSiZr), ferro silicon manganese (FeSiMn) and ferro silicon (FeSi 65%) ferroalloys have been investigated for nuclear radiation attenuation properties. For this aim, linear attenuation coefficients (LAC) were measured using Lambert-Beer law for transmission of the gamma rays at 81, 356, 661, 1173 and 1332 keV photon energies emitted from 133Ba, 137Cs and 60Co radioactive sources to irradiate the ferroalloys. The mass attenuation coefficient (MAC), halfvalue layer (HVL), tenth-value layer (TVL), and mean free path (MFP) of ferroalloys were then determined using LACs in the same photon energies. Effective atomic numbers (Zeff) of ferroalloys were also obtained using total atomic cross-sections (sigma a) calculated from MACs in the same photon energies. HC ferroalloy was found the best radiation shielding material due to the lower MFP and higher MAC values at the interested gamma ray energies at transmission geometry. The ferroalloys were also compared with some standard radiation shielding concretes. It was concluded that the ferroalloys showed better radiation shielding characteristics on behalf of MFP values at 356 keV photon energy. The studied ferroalloys have better MFPs between 2.91% (for FeSi 65%) and 66.81% (for HC) differences than standard concretes.
Keywords: Ferroalloys; Mean free path; Radiation attenuation; Gamma-ray shielding; Tenth value layer